Pengaruh Konten Media Sosial, E-wom, Dan Product Quality Terhadap Minat Beli Konsumen Kantilan Food : The Influence of Social Media Content, E-wom, and Product Quality on Consumers Purchase Intention at Kantilan Food - Abrian Zelta Fernando; Roni Nur Triwibowo; Fajar Nurwibowo (Jurnal Ilmiah Produktif, 2026)
This study explores the impact of social media content, Electronic Word of Mouth (eWOM), and product quality on consumers’ purchase intention toward Kantilan food. A quantitative survey method was employed, involving 100 selected respondents via purposive sampling. Data analysis was conducted using SPSS 26, the research utilized various analytical technique such as data quality testing, classical assumption testing, and multiple linear regression analysis, followed by hypothesis testing through the t-test, f-test, and coefficient of determination. The findings indicate that, individually, social media content and product quality significantly influence purchase intention, with respective p-values of 0.003 and 0.000 both below the 0.05 significance threshold. However, eWOM does not significantly affect purchase intention (p = 0.124). Collectively, however, all three variables significantly influence purchase intention (p = 0.000).